‘What Do Children Think About AI?’: Insights and Educational Implications from Primary School Students’ Perceptions of AI - Kasinidou, Maria; Kleanthous, Styliani; Otterbacher, Jahna (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
AI has great potential to transform education and daily life. However, before integrating AI into classrooms, it is crucial to first educate children on what AI is and how to use it responsibly. Effective AI education should build on children’s existing perceptions, address misconceptions, and establish a solid foundation for AI literacy. This study explores primary school students’ perception of AI and its relationship to their demographic characteristics and digital skills. A survey was conducted in seven local schools, with 233 students participating. The results indicate that most of them were unfamiliar with AI, and those who attempted to define or depict it often associated it with robots or digital devices. The study also found significant differences in students’ AI perceptions based on factors like gender, grade, and prior digital skills training. These variables were also linked to students’ awareness and understanding of AI. These findings underscore the need for targeted AI educational interventions for primary school students, leveraging their existing perceptions.